The Role of Family in Shaping Political Affiliation in Bangladesh: A Comprehensive Observation - Md. Sayedur Rahman; Most. Nilufar Yesmin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Family is the primary agent of political socialization. There are some roles of the family toward their younger members in shaping political affiliation. The title of this research is “The Role of Family in Shaping Political Affiliation in Bangladesh: A Comprehensive Study”. The objectives of this research work are 1) To investigate the overall scenario of the role of the family in shaping political affiliation 2) To investigate and analysis the role of the family in causing political affiliation and apolitical affiliation. The rationality of this study is to create awareness in rural Bangladesh. As a result of this research work, the families are engaged to be more conscious about their role in the political socialization of next-generation and family bondage is expected to be more transparent among family members. The rural people are expected to be more concerned about their growing up children. Beck, P. A. (1991) and Jennings, M. K. (2009) are working mention three roles of family or parents. These are: parents play an important role in the political education of their offspring; children are more likely to adopt their parents’ political orientations if the family is highly politicized, and early acquisition of parental political characteristics influences the political character and behavior during their adulthood. For this research, I have selected a typical Bangladeshi Union namely Bhendabari under Pirgang Upozilla in the northern Bangladeshi district of Rangpur. This study is both qualitative and quantitative. Political socialization can be included in the academic syllabus.